(untitled) (Bangladesh Journal of Agriculture, 2022)
An experiment was conducted at Agronomy Farm of Bangladesh Agricultural University, Mymensingh (BAU) during rabi season of 2018−19 to see the response of garden pea to manure and fertilizers. The treatments were T1: Control (no fertilizer or manure), T2: Cowdung + Poultry manure + Mustard oilcake, T3: Vermicompost + Poultry manure + Mustard oilcake, T4: Urea + TSP + MoP + Gypsum and T5: Cowdung + Urea + TSP + MoP + Gypsum. The experiment was designed in a factorial Randomized Complete Block Design (RCBD) with 4 replications. Urea, TSP, MoP and gypsum @ 45, 90, 40 and 50 kg ha−1 were used as sources of nitrogen, phosphorous, potassium and sulphur, respectively. Cow dung, poultry manure, vermicompost and mustard oilcake were applied @ 30, 25, 2.5 and 0.025 t ha−1, respectively. The results showed that the treatment T5 significantly gave the highest values of vegetative growth and yield attributing characters’ i.e., plant height, number of branches per plant, number of pods per plant, pod length, pod breadth, number of seeds per pod, 100-seed weight, pod weight, pod yield and seed yield per hectare. The lowest values of growth and yield attributing characters were recorded with T1. Sole chemical fertilizers (T4) showed better performances than T2 and T3. Treatment T5 gave higher result than T4. So, for obtaining the highest growth and pod yield of pea (cv. BARI Motor3), treatment T5 (Cowdung + Urea + TSP + MoP + Gypsum @ 30 t ha−1, 45-90-40-50 kg ha−1) could be the best combination. Bangladesh J. Agri. 2022, 47(1): 121-129